DISTRIBUTION OF UNDERGROUND DRAIN OF CATCHMENT BASIN OF SEVAN LAKE: (according to the data of electrosounding and drilling) (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
Studying the distribution of underground runoff, the main issues are: a) determination of the spatial distribution and concentration of the underground runoff, having its total value (according to the water balance data); b) assessment of the estimated costs of individual paleolines for solving problems (interception of underground runoff at high elevations). Based on the critical analysis and reinterpretation of this material (mainly VEZ data), we compiled a new summery map at a scale of 1: 50 000 and sections for the regional water basin (paleorelief) of the entire catchment basin of Sevan Lake. Taking into account the fact that the regional water confinement is the main distributor of underground flow, the compiled paleorelief maps and sections provide objective information about the ways of passing the concentrated underground flow and propitious areas for their interception.
Keywords: Gegama Ridge; Vardenis Ridge; underground drain; Lake Sevan basin; watershed; concentrated watercourse; Darcy formula; electrosounding; drilling holes; groups of springs